Evaluasi Kesuksesan Implementasi Multimedia Auto Recording Smart Hybrid Classroom (MASH Classroom) untuk Mahasiswa Fakultas Ilmu Komputer Universitas Brawijaya menggunakan Unified Theory of Acceptance and Use of Technology (UTAUT) - Rizka Amalia Zeny Putri; Admaja Dwi Herlambang; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Evaluation towards the success of MASH Classroom's implementation is required to gain the recommendation that can be used for improving its implementation success' rate. The evaluation is done by using four variables from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, which are performance expectancy, effort expectancy, social influence and facilitating conditions. Quantitative research method with descriptive statistics in this research includes 1273 MASH Classroom user students at FILKOM UB as its population. The samples are determined with Slovin's equation with 10% of error tolerance which obtained 96 MASH Classroom user students at FILKOM UB as the research sample. The results showed that performance expectancy (50,68%), effort expectancy (53,80%), social influence (62,40%) and facilitating conditions (56,20%) is in the neutral category. Recommendations given according to the research results are emphasizing the delivery of RPS in each semester, provision of task-spesific human resource for daily operationalization of the class, allocating MASH Classroom for non-academic student activities, and emphasizing computer-supported collaborative learning (CSCL) by the lecturers through workshop and training.